Patient with Infiltrating Ductal Cell Carcinoma Mammae with Lung Tuberculosis and Nontuberculous Mycobacteria - Indah Sari, Fitri; Sugiri, Yani Jane; Nurhidayati, Dwi Yuni (Universitaas Brawijaya, 2021)
Introduction:. Infection caused by NTM has a prevalence which varies between 4.1 and 14.1 per 100,000 patients per year. Female has a higher prevalence of NTM disease than male, which is increasing with age, and more common in Western and Southeast Asian countries.Case Description: A 42-year-old female patient has the clinical symptoms of hemoptysis, asphyxia, angina, fever, nocturnal hyperhidrosis, loss of weight and appetite for nearly 10 years. Based on the physical examination, radiology, microbiology and anatomic pathology, this patient has been diagnosed with Ca mammae with Pulmonary TB, and currently is infected by recurrent NTM.Discussion: Symptoms of nonspecific NTM often complicate the diagnosis of TNM. General symptoms such as chronic cough, increased sputum production, dyspnea, fever that is not too high, weakness, weight loss so that it overlaps with other pulmonary symptoms. In NTM, radiologicalmanifestations generally show bronchiectasis, nodular lesions, cavitary lesions and parenchymal consolidation. The choice of therapy in disease caused by NTM depends on three factors: the type of clinical presentation, the species of NTM causing the disease and the immune status of the patient.